Evaluation of the Dengue Hemorrhagic Fever Eradication Program in Palembang - Galuh Ismayanti; Chairil Anwar; Rizma Adlia Syakurah; Ahmad Ghiffari; Ramzi Amin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Dengue Haemorrhagic Fever (DHF) has the potential to cause Extraordinary Events (KLB), hence the government has made efforts to control DHF, one of which is through the PSN program. Evaluation is necessary to determine how the implementation of the PSN program is following the planned objectives and whether the program can control the breeding of mosquito larvae to reduce the number of dengue cases in Palembang City. Methods: This study utilized a qualitative method with an analytical descriptive approach. The CIPP evaluation model was used to evaluate the context, input, process, and product to determine the success of the PSN program. The information was obtained from twelve informants who were recruited by purposive sampling. Results: The study data was collected in the form of interviews, observations, and a document review to evaluate the dengue fever mosquito nest eradication program (PSN) in Palembang City in 2022. In general, the PSN program has gone well but is still constrained by budget. Furthermore, SOPs related to eradicating mosquito nests do not yet exist and there is a lack of community participation. Conclusion: It is anticipated that Palembang City Health Office can use these study findings as a basis to justify budget allocation for the mosquito nest eradication program and develop SOPs regarding the eradication of mosquito nests to facilitate the program. They could also improve coordination, participation, and community empowerment to implement a larva-free village competition and providing a reward for villages that have been declared larva-free by the Puskesmas to encourage community participation in the eradication of mosquito nests.